Aberrant Overexpression of the Cell Polarity Module Scribble in Human Cancer - Vaira, Valentina (American Society for Investigative Pathology, 2011)
Human Scribble (Scrib) is an evolutionary-conserved cell polarity protein, but its potential role in human cancer is controversial. Herein, we show that Scrib is nearly universally overexpressed in cultured tumor cell lines and genetically disparate cancer patient series compared with matched normal tissues in vivo. Instead of a membrane association seen in normal epithelia, tumor-associated Scrib is mislocalized and found predominantly in the cytosol. Small-interfering RNA silencing of Scrib in model lung adenocarcinoma A549 cells inhibited cell migration in wound-healing assays, suppressed tumor cell invasion across Matrigel-coated inserts, and down-regulated the expression of cell motility markers and mediators of epithelial-mesenchymal transition. These data uncover a previously unrecognized exploitation of Scrib for aberrant tumor cell motility and invasion, thus potentially contributing to disease progression in humans.